Cardiac cachexia. (23rd December 2019) - Lena, Alessia; Ebner, Nicole; Anker, Markus S
Abstract: Cachexia is a multifactorial disease characterized by a pathologic shift of metabolism towards a more catabolic state. It frequently occurs in patients with chronic diseases such as chronic heart failure and is especially common in the elderly. In patients at risk, cardiac cachexia is found in about 10% of heart failure patients. The negative impact of cardiac cachexia on mortality, morbidity, and quality of life demonstrates the urgent need to find new effective therapies against cardiac cachexia. Furthermore, exercise training and nutritional support can help patients with cardiac cachexia. Despite ongoing efforts to find new therapies for cachexia treatment, also new preventive strategies are needed.